2000
DOI: 10.1051/aas:2000274
|View full text |Cite
|
Sign up to set email alerts
|

Dust features in the 10-μm infrared spectra of oxygen-rich evolved stars

Abstract: Abstract.We have analyzed the 8 − 13.5 µm UKIRT CGS3 spectra of 142 M-type stars including 80 oxygenrich AGB stars and 62 red supergiants, with a view to understanding the differences and similarities between the dust features of these stars. We have classified the spectra into groups according to the observed appearance of the infrared features. In each case the normalized continuumsubtracted spectrum has been compared to those of the other stars to find similarities and form groups. The dust features of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
226
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(243 citation statements)
references
References 41 publications
(76 reference statements)
15
226
2
Order By: Relevance
“…It is an M8-9-type Mira Ceti variable found by Wolf (1904) with P = 424.75±1.77 d (Templeton et al 2005) and silicate dust emission (Sloan & Price 1998;Speck et al 2000). In particular, the 9.7 and 18 µm silicate dust feature originates from the circumstellar envelopes of oxygenrich asymptotic giant branch stars (Kwok et al 1997).…”
Section: Known Background Giants X Ori (No 29)mentioning
confidence: 91%
“…It is an M8-9-type Mira Ceti variable found by Wolf (1904) with P = 424.75±1.77 d (Templeton et al 2005) and silicate dust emission (Sloan & Price 1998;Speck et al 2000). In particular, the 9.7 and 18 µm silicate dust feature originates from the circumstellar envelopes of oxygenrich asymptotic giant branch stars (Kwok et al 1997).…”
Section: Known Background Giants X Ori (No 29)mentioning
confidence: 91%
“…In fact, all three dust species discussed in this paper have been proposed as carrier of the 13 μm band. Speck et al (2000) propose (amorphous) SiO 2 as feature carrier, Posch et al (1999) and Fabian et al (2001) favor MgAl 2 O 4 , Sloan et al (2003) and DePew et al (2006) have strengthened the case for α-Al 2 O 3 . It should be noted that this dust feature has also been detected in AGB stars outside our galaxy (e.g.…”
Section: Consequences Of Our Measurements For the Astronomical 13 μM mentioning
confidence: 97%
“…When comparing the distribution in colors of the 119 RSG stars in clusters with all RSGs listed by Skiff et al, however, no significant differences are seen. Verhoelst et al (2009) studied the dust properties of O-rich RSGs envelopes and found a dust condensation sequence resembling that of AGBs (Kemper et al 2001;Speck et al 2000;Sylvester et al 1999). Stars with low mass-loss rates are rich in oxides and alumina, while high mass-loss stars show olivine, and crystalline silicates (Waters 2010).…”
Section: Red Supergiant Starsmentioning
confidence: 99%